Literature Review on Characterization and Optimization of Protease Enzymes for Medical Applications - Ananta, Yorasakhi (Dinasti Health and Pharmacy Science, 2024)
Protease enzymes are a group of enzymes that play an important role in protein breakdown and have been widely studied for medical applications, especially in the fields of wound healing, cancer therapy, and antimicrobials. This article presents a systematic review of various studies exploring the biochemical characterization and optimization of protease enzyme activity produced by microorganisms. The main focus of this review includes the optimum conditions for enzyme activity, stability to pH and temperature, and genetic engineering and fermentation methods for increasing its production. It was found that thorough characterization is very important in determining the potential for clinical application of protease enzymes. In addition, optimization of enzyme production through fermentation and biotechnology approaches has been shown to increase efficiency and reduce the risk of side effects in medical applications. This review provides a comprehensive overview of the progress and challenges in the development of proteases for use as therapeutic agents.